PROBLEMATICS AND POETICS OF GALYNA ORLIVNA’S NARRATIONS OF THE 1930s - Zhylenko, Iryna; Vedmydera , Karyna (Philological Treatises, 2022)
The article focuses on the periodisation of creative works of the Ukrainian writer Halyna Orlivna, identifies peculiarities of the problematics, and studies artistic means in her narrations of the Kharkiv period. It is emphasized that after returning from emigration, Galyna Orlivna engages herself actively into current problems of those times, such as changed village life, topics regarding collectivisation, and construction of socialism. Her views onto these are reflected in her works in socialist realism. Particular attention is drawn to the fact that the main character of the writer’s narrations (“Babskyi bunt” (Women’s Uprising), “Ilishva”, etc.) is represented by a strong and willful female character, capable of high feelings and unexpected actions, both in her personal and social life. It is pointed out that one perceives modernist aesthetics in Galyna Orlivna’s works of the Kharkiv period, where the author reveals deep psychological features of her characters while involving a broad range of artistic means and techniques (symbolism of eyes, dreams, metaphorisation, and musicalisation).